Students’ reflective thinking based on their levels of emotional intelligence in mathematical problem-solving - Dwi Priyo Utomo; Erentrudis Junirestu; Arif Hidayatul Khusna (Universitas Islam Negeri (UIN) Mataram, 2021)
[English]: This qualitative research aims to analyze secondary students’ reflective thinking in solving mathematical problems based on their emotional intelligence (EI). It involved four secondary school students selected from twenty-nine students who were given the EI questionnaire. The research instrument was a test and an interview guideline. Data analysis was referred to as Polya's four problem-solving stages integrated with the indicators of reflective thinking. The findings reveal that students with a high level of emotional intelligence can fulfill the whole indicators of reflective thinking. In this case, the students can react to a given situation or problem by carefully understanding the available information, making comparisons between elements to formulate strategies, explaining in detail the steps to solve problems, and doing contemplation in checking step by step and correcting mistakes. Meanwhile, students with mid-levels of emotional intelligence are less reflective in making comparisons between elements to formulate strategies for problem-solving. [Bahasa]: Penelitian kualitatif ini bertujuan untuk menganalisis pemikiran reflektif siswa sekolah menengah pertama dalam menyelesaikan masalah matematika berbasis kecerdasan emosional. Subjek penelitian adalah empat siswa, dipilih dari 29 siswa yang mengisi kuesioner. Data dikumpulkan melalui tes dan wawancara kemudian dianalisis dengan merujuk pada empat langkah pemecahan masalah Polya yang diintegrasikan dengan indikator berpikir reflektif. Hasil penelitian ini menunjukkan bahwa siswa dengan tingkat kecerdasan emosional tinggi memenuhi semua indikator berpikir reflektif dalam pemecahan masalah. Dalam hal ini, siswa mampu memberikan reaksi pada situasi atau permasalahan yang diberikan dengan memahami secara cermat informasi yang ada, melakukan komparasi antar elemen untuk menyusun strategi, menjelaskan secara rinci langkah memecahkan masalah, melakukan kontemplasi dalam memeriksa langkah demi langkah dan memperbaiki kesalahan. Sedangkan siswa dengan tingkat kecerdasan emosional sedang kurang reflektif dalam melakukan komparasi antar elemen untuk menyusun strategi pemecahan masalah.